Anti-inflammatory effects of Eclipta prostrata Linné on house dust mite-induced atopic dermatitis in vivo and in vitro. (28th June 2022) - Kang, Yun-Mi; Kim, Hye-Min; Lee, Hwan; Lee, Dong-Sung; An, Hyo-Jin
Abstract: Ethnopharmacological relevance: Atopic dermatitis (AD) is a kind of inflammation on the skin following with swollen, itchy, dryness and cracked skin. Though the exact cause of AD is unknown, there are evidence that people with AD have a compromised skin barrier along with inflammation. Eclipta prostrata Linné is a traditional herbal medicinal plant, has been used for the diabetes, obesity, jaundice, and inflammation. We supposed E. prostrata L. has an anti-inflammatory effect on the skin. Aim of the study: We aimed to assess the effect of E. prostrata L. EtOH extract (EP) and elucidate the associated molecular mechanisms. Materials and methods: The effect of EP and the molecular mechanisms were eluciated in house dust mite (HDM)-induced AD mice model and TNF-α/IFN-γ-stimulated HaCaT keratinocytes by histological analysis, enzyme-linked immunosorbent assay, quantitative real time polymerase chain reaction, and Western blot. Results: The results revealed that EP improved the progression of AD symptoms, decreasing epidermis/dermis thickness, infiltrated immune cells, and restored the skin barrier dysfunction and imbalanced immune response. EP suppressed the expressions of T helper (Th)1, Th2, Th17 cytokines, phosphorylation of extracellular signal-regulated kinase/signal transducer and activator of transcription 1 in skin of HDM-induced AD mice as well as inhibition the translocation of nuclear factor-κB in HaCaT keratinocytes. Conclusions: Collectively, EP improved the allergic inflammation of the skin through recovery the skin barrier, and regulation the immune balance. These results suggest EP may have therapeutic potential as an anti-atopic agent. Graphical abstract: Image 1